2021
DOI: 10.18231/j.ijca.2021.036
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia management of renal transplantation: A retrospective analysis

Abstract: Transplantation provides a near normal life and excellent rehabilitation compared to dialysis and is preferred method of treatment for end stage renal disease patients. After ethics committee approval, a retrospective analysis of recipients of renal transplantation was done at our hospital from January 2010 to December 2014. Preoperative patient status, fluid management, hemodynamic parameters, anesthesia management, and perioperative complications were recorded and analyzed.Total 100 patients were recorded,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Milrinone is a positive inotrope and a vasodilator. Optimization of intravascular fluid management for good renal perfusion while avoiding fluid overload and vigilant hemodynamic monitoring is essential for successful outcome (Tiwari et al 2021;Reyle-Hahn et al 1997). Excessive blood loss should be replaced with blood in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Milrinone is a positive inotrope and a vasodilator. Optimization of intravascular fluid management for good renal perfusion while avoiding fluid overload and vigilant hemodynamic monitoring is essential for successful outcome (Tiwari et al 2021;Reyle-Hahn et al 1997). Excessive blood loss should be replaced with blood in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…N) in 4 (4.3%) and hereditary nephropathy in 3 (3.2%) were common reasons for end stage kidney disease. Tiwari et al, [9] included 100 patients with end stage renal disease and found that 92% were living and 8% were cadaveric related transplant. 92% were done electively.…”
Section: Discussionmentioning
confidence: 99%